Problematics of Physical Education Teachers in Modifying PJOK Learning Media at Public Primary School In Herlang Bulukumba - Putra, Syah Risal; Arimbi; Yasriuddin; Ridwan, Andi; Hudain, Muh Adnan (Indonesian Journal of Physical Activity, 2024)
In the learning process, there are many challenges faced by physical education teachers at schools, particularly in providing a comfortable learning environment for students. Physical education teachers need to be able to offer engaging learning experiences, whether using tools or making modifications, so that PJOK (Physical Education, Sports, and Health) lessons are enjoyable for students. This research was conducted to understand the challenges faced by physical education teachers in modifying PJOK learning media in elementary schools using descriptive qualitative research methods. Data analysis shows that 1 physical education teacher falls into the excellent category with a percentage of 12.5%, 1 teacher is in the good category with a percentage of 12.5%, 4 teachers are in the moderate category with a percentage of 50%, 1 teacher is in the less good category with a percentage of 12.5%, and 1 teacher is in the poor category with a percentage of 12.5%. The contributing factors include, firstly, inadequate facilities and infrastructure at the school, which do not support the learning process, causing difficulties for the teachers as many students struggle to grasp the material. Second, the relatively low level of creativity among physical education teachers in teaching PJOK. Thirdly, the high workload, especially due to their responsibilities for numerous extracurricular activities and sports at the school, in addition to their classroom teaching duties. The conclusion of this research is that the inadequate facilities and infrastructure, relatively low creativity levels among teachers, and the high workload are significant challenges